Inclusive teacher competence as a component of professional training - Pavlyshyna, Nataliia; Kuzava, Iryna (Wydawnictwo Wyższej Szkoły Technicznej w Katowicach, 2024)
This article examines the characteristics of developing inclusive competence as a key component of teacher professional training in higher education institutions. It analyzes definitions of the terms "inclusion," "professional training," and "inclusive competence." The essential competencies of teachers in inclusive education, which are necessary for performing professional tasks, are highlighted. The key components of inclusive competence, which ensure the provision of educational services at a high level, are identified. The structure of a teacher’s inclusive competence and the specifics of its formation within higher education institutions are also defined.
Keywords: Professional competence; Inclusion; Inclusive competence; Professional training